Financial Risk Management in Facing the Economic Crisis in Bangka Belitung Province - Suhardi Suhardi (Nomico, 2025)
This research article discusses the importance of financial risk management in facing the economic crisis in Bangka Belitung Province, this region has great economic potential, especially in the mining and tourism sectors, but is also vulnerable to the global economic crisis, this study aims to analyze the condition of financial risk management in Bangka Belitung Province and identify the types of financial risks faced by companies and financial institutions. This study uses a case study method and secondary data analysis from provincial economic reports, the results of the study indicate that Bangka Belitung Province has relatively stable economic growth, but still faces significant financial risks, therefore effective financial risk management is needed to face the economic crisis. Effective financial risk management can help companies and financial institutions in Bangka Belitung Province to identify, measure and manage financial risks effectively, this can be done by developing appropriate risk management strategies, improving credit quality and strengthening the stability of the financial system. Thus, this study can contribute to the development of financial risk management in Bangka Belitung Province and help companies and financial institutions to face the economic crisis better, this study can also be a reference for local governments and related institutions in developing policies to improve the economic resilience of Bangka Belitung Province